Ride on - Australia. Office of Road Safety ([Canberra] : Federal Office of Road Safety, 1998)
Designed to help students and instructors in the art of safe motorcycle riding.
"A new approach to safe rider training. Made by motorcyclists for motorcyclists." --Container jacket.
Presenter: Wayne Gardner.
Keywords: Motorcyclists -- Training of -- Australia